New Nonwoven Fabrics for Pollination Control Bags for Oil Palm: New pollination bags for oil palm - Light, Marnie E; Virk, Daljit Singh; Senior, Hannah (International Journal of Oil Palm, 2023)
Oil palm hybridisation requires the isolation of inflorescences with pollination control bags (PCBs) for which polyester duraweb® PCBs are used at the Dami Oil Palm Research Station in Papua New Guinea. For widening the choices of nonwoven PCBs we compared the performance of PCBs from three new types of nonwoven fabrics with the standard duraweb® PCB on 9-year-old clonal palms in one of the Dami SUPERFAMILY® seed gardens. The station typically experiences a humid climate and received weekly total rainfall ranging from 53 to 228 mm (total rainfall 1035 mm) during the reproductive phase in March and April 2020, when the trial was conducted. Analyses of variance of a number of traits such as time taken to install the bags, bag intactness, spine damage and water absorption of bags, bunch weight, healthy and total seed number and weight, seed health score, and 100-seed weight were all non-significant. The average number of healthy seeds per bunch was 1120 seeds with mean weight of 376 g per 100 seeds. Blank pollinations showed equal pollen-proofing ability among all bags without any noticeable insect entry. This study, for the first time, has identified three other nonwoven fabric PCBs with no statistical differences from the control duraweb® bags for most of the important traits, and provides new alternatives to reduce the dependency on only one type of fabric which, when in short supply, could adversely affect the plant breeding and seed production programmes.